Effect of molasses on nutritive value and in-vitro digestibility of elephant grass silage - Ayandiran Samuel Kola; Odeyinka Simisola Mercy; Oloidi Festus Femi; Amoo Ase-Oro Falilat; Ojo Iyanu Faith; Ogunmola Yetunde Esther; Olakunle Toyin Margret (Agricultura Tropica et Subtropica)
Ensiling preserving a forage crop and its nutrients to feed later on as silage. In this study, elephant grass was ensiled with varying levels of molasses as an additive to evaluate its effect on the nutritive value and in-vitro digestibility of the silage. Four treatments of Pennisetum purpureum grass silage were produced with the inclusion of molasses at 0 (T1), 2.5 (T2), 5 (T3), and 7.5 % (T4) inclusion levels. Elephant grass ensiled with higher levels of molasses inclusions (T3, and T4) had significantly higher (p < 0.05) dry matter, crude protein, nitrogen-free extract, and lactic acid than T1 and T2 silages. However, T1 and T2 silages had significantly higher (p < 0.05) crude fibre and ash contents. Furthermore, silage without molasses inclusion (T1) had significantly higher (p < 0.05) in most of the fibre fractions compared to other silages in this study. At 6 and 15 hours, there were no significant differences (p > 0.05) in the means of in-vitro gas production. However, gas production was significantly higher (p < 0.05) in silages with the inclusion of additives (T4, T3, and T2) at 9, 12, 18, 21, and 24 hours of incubation. Conspicuously, silages containing graded levels of molasses as an additive had significantly higher (p < 0.05) digestibility and organic matter digestibility than the silage without molasses. The methane gas and metabolisable contents were significantly higher (p < 0.05) in T3 and T4 silages than T1 and T2 silages. However, T3 had significantly the highest (p < 0.05) gas volume followed by T2, T4, and T1 silages. It can be concluded that our H1 hypothesis was confirmed and the inclusion of molasses as an additive in elephant grass silage resulted in improved dry matter, crude protein, lactic acid contents, reduced fibre fractions, and superior in-vitro digestibility values as well as relatively better gas production by the silage.